Moving Beyond Churn: Barriers and Constraints to Playing a Social Network Game. Issue 2 (March 2019) - Bergstrom, Kelly
Social network games (SNGs) are genre of casual games that require being logged into a social networking site (e.g., Facebook) to access the gameworld. To date, investigations of these games are typically focused on the rate of attrition or "churn, " reinforcing the idea that SNG players exist to make the developer money rather than participating in a game they derive pleasure from. Seeking to recenter the player in research about SNGs, this article reports on a survey of former players ( N = 147) who were queried about their reason(s) for no longer participating in YoWorld, a Facebook-based SNG. Findings indicate that players typically quit because of external constraints to their leisure time rather than no longer interested in the game, which are not barriers to play that can be overcome by personalized in-game incentives, the typical developer response to prevent churn from taking place.